UJI EFEKTIFITAS E-MODUL TRIGONOMETRI BERBASIS SCHOOLOGY UNTUK PEMBELAJARAN DARING DI POLITEKNIK - I Gde Nyoman Sangka (Jurnal Pembelajaran dan Pengembangan Matematika, 2021)
The purpose of the study was to determine the level of validity, practicality, and effectiveness of the E-Module Trigonometry. The research uses the ADDIE model development research approach with stages: Analysis, Design, Development, Implementation, and Evaluation. The implementation is in the Department of Electrical Engineering, Bali State Polytechnic. Data were collected using a validation questionnaire, practicality questionnaire, pretest and posttest of trigonometric competence. Validation includes aspects: content feasibility, presentation, language, and graphics carried out by experts and practitioners. Practicality through trials: small groups, large groups and limited trials. The subjects are students and mathematics lecturers. Effectiveness through t test data pretest and posttest in the experimental and control groups. The subject is student. The data were analyzed descriptively, the results showed the level of validity reached 81.9%, categorized as valid. The level of practicality through practicality tests by lecturers is 82.0% which is categorized as practical with minor revisions and the level of practicality through practical tests by students is 81.8% categorized as practical with minor revisions. The results of the independent sample test showed that there was a significant difference (sig.0.000) between learning outcomes using e-modules and without e-modules. The results of the paired t test of the experimental group showed the correlation coefficient between the initial ability (before) and the final ability (after) the learning process with the E-Module of 0.707 categorized as positive, strong and significant. Thus, the E-Module is declared feasible, practical, and effectively used as teaching material.